Analisis Kemiskinan Di Provinsi Sulawesi Tenggara - Andriani Andriani; Teguh Permana (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The aim of this research is to classify regencies and cities in Southeast Sulawesi province based on poverty indicators. The method used is descriptive quantitative using cluster analysis with SPSS software. The data used is secondary data originating from BPS in the form of cross-sectional data for 2022 which consists of the poverty depth index, the percentage of poor people and the poverty severity index. Based on the results of the analysis, poverty at the district and city levels in the province of Southeast Sulawesi is divided into 3 groups. Group 1 consists of the city of Kendari and the city of Bau-Bau. Group 2 consists of Buton Regency, Muna Regency, Kolaka Regency, South Konawe Regency, Bombana Regency, Wakatobi Regency, East Kolaka Regency, West Muna Regency, Central Buton Regency and South Buton Regency. Group 3 consists of Konawe Regency, North Kolaka Regency, North Buton Regency, North Konawe Regency and Konawe Archipelago Regency. Based on cluster analysis, regencies and cities that have the highest poverty are in group 3, moderate poverty is in group 2 and the lowest poverty is in group 1